2004
DOI: 10.1213/01.ane.0000101601.43781.15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Effects of Signal Integrity and Saturation on Data Availability and Accuracy of Masimo SET?? and Nellcor N-395 Oximeters in Children

Abstract: We compared new pulse oximeters from Nellcor and Masimo and found that, with good signal conditions, both new devices performed similarly to older technology. Overall, Masimo reported less data as questionable than Nellcor. With poor signal conditions or during hypoxemia, the new devices are not clinically equivalent to each other or to the older technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Figure 3 strongly suggests that airway obstruction occurred during this episode, with paradoxical movements of the chest and abdominal tracing coincident with the sudden fall in SpO2. The accuracy of pulse oximeters is poor at low SpO2's (26); nevertheless, this infant was considered by two experienced physicians to be deeply cyanosed during the episode.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 strongly suggests that airway obstruction occurred during this episode, with paradoxical movements of the chest and abdominal tracing coincident with the sudden fall in SpO2. The accuracy of pulse oximeters is poor at low SpO2's (26); nevertheless, this infant was considered by two experienced physicians to be deeply cyanosed during the episode.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the newer generation of oximeters like those incorporated with the signal extraction technology (SET R ) from the Masimo Corporation (Irvine, California, USA) shows promising results (Salyer 2003, Trivedi et al 1997. However, conflicting reports on their performance do exist (Robertson andHoffman 2004, Bohnhorst et al 2000). Although an accurate SaO 2 measure from modern oximeters may be achieved, the characteristics of its other serial output signals like the photoplethysmography (PPG) have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of SpO 2 monitors with signal extraction technology (Masimo SET) during situations of low perfusion and motion have been previously described. [7][8][9][10][11] SpO 2 monitoring is based on the relation between hemoglobin (Hb) and oxygen. Bohr showed that the dissociation curve was sigmoid shaped, with an initial relative horizontal portion, followed by a vertical one, ending again with a horizontal shape.…”
Section: Arterial Oxygen Saturationmentioning
confidence: 99%
“…Since some monitors are better than others, a similar or even larger disparity in SpO 2 simultaneous readings between different SpO 2 monitors exists. [7][8][9][10][11]16 When SpO 2 is 97% in one monitor, the true SaO 2 and the SpO 2 in another monitor could be 100%. Therefore, accepting the imprecision of the real world, the one SpO 2 value cannot be the sole focus.…”
Section: Tension Of Arterial Oxygen (Pao 2 )mentioning
confidence: 99%